Wędrówki po definicjach.Znaczenia terminów „nowoczesny”/„nowoczesność”/„modernizm” - Stanford Friedman, Susan (Poznańskie Studia Polonistyczne. Seria Literacka, 2014)
<span style="font-family: 'Times New Roman','serif'; font-size: 12pt; mso-ansi-language: EN-US; mso-fareast-font-family: 'ＭＳ 明朝'; mso-fareast-theme-font: minor-fareast; mso-fareast-language: PL; mso-bidi-language: AR-SA;" lang="EN-US">The main task of the present article is to characterize the changing perspectives in the description and definition of modernism and modernity in a reciprocal relationship of these two categories. The creation of definitions is described here as a processes of fictionalization with a generational viewpoint of scholars. Moreover, the article indicates the difference between a nominal and a relational mode of defining and the question of institutionalization of knowledge within the framework of definition projects. Such research perspectives lead to the conclusion about dialogical and at the same time contradictory character of historical formations of phenomena to which the studied terms allude.